Sistem Informasi Penggajian Pegawai Berbasis Desktop pada CV.Hijab Geulis Konveksi - Setiawan, Topan (Masoem University, 2025)
The payroll process is a critical component of company operations, including in the garment manufacturing (konveksi) industry. However, manual payroll management often leads to various issues such as calculation errors, delayed payments, and inefficiencies in report generation. This study aims to design and develop a desktop-based employee payroll information system to enhance the effectiveness and accuracy of payroll management at CV.Hijab Geulis Konveksi. The research uses the Research and Development (R&D) method with a Agile approach in software development. The system was built using Visual Basic .NET programming language and MySQL as the database. Key features of the system include employee data management, attendance recording, automated payroll calculation, payslip generation, and payroll reporting. Testing results show that the system functions effectively, reduces calculation errors, and accelerates the payroll process. With its simple and user-friendly interface, the system can be easily operated by non-technical users. In conclusion, this desktop-based payroll information system offers an effective solution to support administrative payroll tasks in small to medium-scale garment manufacturing companies.